1992
DOI: 10.1093/tropej/38.4.173
|View full text |Cite
|
Sign up to set email alerts
|

Septicaemia among Neonates with Tetanus

Abstract: In a study of 149 cases of neonatal tetanus (NNT) admitted into the University of Calabar Teaching Hospital, 49 (33 per cent) were also found to have septicaemia. The dominant organisms were coliforms and Staphylococcus aureus. A comparison of the clinical features of the septicaemic and non-septicaemic neonates showed umbilical cord infection to be an indicator of septicaemia. There was no significant difference in the case fatality rates of the two groups of patients and the overall case fatality was low (37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 0 publications
2
17
1
Order By: Relevance
“…This study confirms that co-morbidities such as sepsis identified in these patients worsen the severity of the illness as previously reported,293031 that about half of the neonates with neonatal tetanus also have sepsis and contribute significantly to neonatal mortality.…”
Section: Discussionsupporting
confidence: 91%
“…This study confirms that co-morbidities such as sepsis identified in these patients worsen the severity of the illness as previously reported,293031 that about half of the neonates with neonatal tetanus also have sepsis and contribute significantly to neonatal mortality.…”
Section: Discussionsupporting
confidence: 91%
“…This study could not ascertain the causative organisms of neonatal septicaemia because results of blood culture and of cerebro-spinal fluid analysis were not available, though Group B Streptococcus, Escherichia coli, Coagulase-negative Staphylococcus, Haemophilus influenzae and Listeria monocytogenes have been identified as common causes of neonatal septicaemia in other parts of the world [27]. Studies in Nigeria however reported 33% of septicaemia among neonatal tetanus cases [28] and 49% of septicaemic neonates in eastern Nigeria [29]. The 61.5% prevalence of There was no statistically significant difference in the mean weight of the 1-day old and with 2-7 days old (df=12.…”
Section: Discussionmentioning
confidence: 92%
“…We found that improved spasm control was achieved by combining continuous midazolam and neuromuscular blockade. Because septicemia is common among neonates with tetanus [8], we believe that the early administration of antibiotics is an important part of routine management.…”
Section: Discussionmentioning
confidence: 99%